2002
DOI: 10.1021/ic011159v
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolylcyclotriphosphazene Containing Pendant Polymers:  Synthesis, Characterization, and Phosphate Ester Hydrolysis Using a Cu(II)-Metalated Cross-Linked Polymeric Catalyst

Abstract: A multi-pyrazolyl cyclotriphosphazene containing polymerizable group N(3)P(3)(3,5-Me(2)Pz)(5)(O-C(6)H(4)-p-C(6)H(4)-p-CH=CH(2)) (2) has been prepared from the corresponding chloro derivative N(3)P(3)Cl(5)(O-C(6)H(4)-p-C(6)H(4)-p-CH=CH(2)) (1). The X-ray structures of 1 and 2 have been determined. Compound 2 undergoes ready metalation with CuCl(2) to afford N(3)P(3)(3,5-Me(2)Pz)(5)(O-C(6)H(4)-p-C(6)H(4)-p-CH=CH(2)).CuCl(2) (3). Model compound N(3)P(3)(3,5-Me(2)Pz)(5)(O-C(6)H(4)-p-CHO).CuCl(2) (6) has been prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 64 publications
(28 reference statements)
3
34
1
1
Order By: Relevance
“…Spectroscopic data are in accordance with that described by Chandrasekhar et al [37] Figure 6. Screening of the bioactivity of various dendrimers towards human monocytes (mfi-R for HLA-DR and CD14 markers).…”
Section: Mono(4-formylphenoxy)pentachloro-cyclo(triphosphazene) (2 A)supporting
confidence: 89%
“…Spectroscopic data are in accordance with that described by Chandrasekhar et al [37] Figure 6. Screening of the bioactivity of various dendrimers towards human monocytes (mfi-R for HLA-DR and CD14 markers).…”
Section: Mono(4-formylphenoxy)pentachloro-cyclo(triphosphazene) (2 A)supporting
confidence: 89%
“…[3][4][5] We and others have been pursuing the possibility of using inorganic cores for building star-burst-type molecules. [6][7][8][9][10][11][12][13][14] Thus, inorganic rings such as cyclophosphazenes, [6,8] cyclosiloxanes, [9] and borazines [10] have been used recently as supports for the preparation of novel compounds which contain a central inorganic core and a periphery of judiciously placed functional substituents. Other inorganic rings and cages that contain Al-N or Al-C units have been similarly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…From the nitrogen analysis it is concluded that every gram of the polymer contains 0.33 g of the cyclophosphazene monomer corresponding to 4.09 × 10 -4 moles. From the AAS analysis the amount of copper present per gram of CPPL-Cu was found to be 21.7 mg. [21] Plasmid (pBR322) modification assisted by the CPPLCu complex was studied in the presence of exogenously added co-oxidants MMPP and oxone. Initial experiments were performed using a varying amount of polymer in the www.eurjic.org presence of MMPP to study the concentration-dependent cleavage of pBR322.…”
Section: Resultsmentioning
confidence: 99%